Tumor-Derived Exosomes Enriched by miRNA-124 Promote Anti-tumor Immune Response in CT-26 Tumor-Bearing Mice - Rezaei, Ramazan; Baghaei, Kaveh; Hashemi, Seyed Mahmoud; Zali, Mohammad Reza; Ghanbarian, Hossein; Amani, Davar (Frontiers in Medicine, 2021)
Exosomes have been introduced as a new alternative delivery system for the transmission of small molecules. Tumor derived exosomes (TEXs) not only contain tumor-associated antigens to stimulate antitumor immune responses but also act as natural carriers of microRNAs. The aim of the current study was to evaluate the efficacy of miR-124-3p-enriched TEX (TEXomiR) as cell free vaccine in the induction of antitumor immune responses in a mouse model of colorectal cancer. Briefly, the exosomes were isolated from cultured CT-26 cell line and modified calcium chloride method was used to deliver miR-124-3p mimic into the exosomes. We used CT-26 induced BALB/c mouse model of colorectal cancer and analyzed the effect of TEXomiR on survival, tumor size, spleen and tumor-infiltrated lymphocytes, and splenocytes proliferation. Furthermore, intra tumor regulatory T cells, cytotoxic activity of the splenocytes, and cytokines secretion was also evaluated to describe the anti-tumor immune response. When tumor size reached 100 mm3, the mice were injected with TEXomiR, TEX, and/or PBS subcutaneously three times with 3-days interval and then tumor size was monitored every 2 days. In vitro results indicated that the TEXs could efficiently deliver functional miR-124-3p mimic. The in vivo evaluation in tumor bearing mice showed that treatment with TEXomiR can elicit a stronger anti-tumor immune response than unloaded TEX and PBS. Significant tumor growth inhibition and increased median survival time was achieved in tumor bearing mice treated with TEXomiR. Significant decrease in CD4/CD8 and Treg/CD8 ratio in tumor tissue was demonstrated. Moreover, increased cytotoxicity and proliferation of splenocytes in TEXomiR group compared to TEX and PBS groups was identified. Taken together, our data demonstrated that tumor derived exosomes efficiently deliver miR-124-3p mimic, and TEXomiR promotes anti-tumor immune responses.